The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.3892/mco.2013.187
|View full text |Cite
|
Sign up to set email alerts
|

Cotargeting EGFR and autophagy signaling: A novel therapeutic strategy for non-small-cell lung cancer

Abstract: Epidermal growth factor receptor (EGFR) somatic mutations are found in the majority of non-small-cell lung cancers (NSCLCs) and patients with NSCLC who harbor EGFR mutations have been shown to exhibit increased sensitivity to the small-molecule EGFR-tyrosine kinase inhibitors (TKIs) gefitinib and erlotinib. However, the majority of tumors develop acquired resistance to EGFR-TKIs after a median of 10-16 months, which limits the clinical efficacy of these drugs. Autophagy, an important homeostatic cellular recyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…Numerous studies have implicated the crucial role of autophagy in cancer chemoresistance (Duffy et al., 2015). However, the exact mechanisms underlying this phenomenon are still unknown and represent a significant barrier to the improvement of the long‐term overcome of NSCLC patients (Kovarik et al., 2014; Sui et al., 2014). Our study highlights for the first time the involvement of autophagy in the metastatic mechanism that drives lung cancer immunosuppressive metastasis and inhibits T cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have implicated the crucial role of autophagy in cancer chemoresistance (Duffy et al., 2015). However, the exact mechanisms underlying this phenomenon are still unknown and represent a significant barrier to the improvement of the long‐term overcome of NSCLC patients (Kovarik et al., 2014; Sui et al., 2014). Our study highlights for the first time the involvement of autophagy in the metastatic mechanism that drives lung cancer immunosuppressive metastasis and inhibits T cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…We found that nintedanibinduced autophagy is ATG7 independent and beclin-1 dependent and thus represents a noncanonical pathway (17,34). Several (37,38) and lymphangioleiomyomatosis (39). Whether such an approach would be beneficial in IPF deserves further study.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy inhibition can overcome both the innate and acquired drug resistance of NSCLC, and thus represents a novel strategy to broaden the spectrum of NSCLC treatment [42-44]. In particular, autophagy inhibition has been exploited to improve the efficacy of small-molecule EGFR-tyrosine kinase inhibitors in the treatment of NSCLC patients [39, 44]. Autophagy inhibitors in current NSCLC clinical trials include hydroxychloroquine (HCQ) and chloroquine (CQ) [39].…”
Section: Discussionmentioning
confidence: 99%